HUBUNGAN DUKUNGAN KELUARGA DENGAN KUALITAS HIDUP ORANG DENGAN GANGGUAN JIWA - Kadek Putra Sanchaya; Ni Made Dian Sulistiowati; Ni Putu Emy Darma Yanti (Persatuan Perawat Nasional Indonesia (PPNI) Jawa Tengah, 2018)
THE RELATIONSHIP BETWEEN FAMILY SUPPORT AND THE QUALITY OF LIFE OF PEOPLE WITH MENTAL DISORDERS ABSTRACTMental disorder is one of the most serious health problems. Families have to spend more time to provide care to People with Mental Disorders at home. People with Mental Disorders (ODGJ) usually have problems with quality of life. The study aimed to determine the relationship between family support and the quality of life of People with Mental Disorders / ODGJ. This research is a quantitative research by using cross-sectional design with correlative analytic method. The sample of the research were 39 people selected by non probability sampling technique of purposive sampling. Data collection of respondent characteristics was conducted by using questionnaire of respondent characteristics. The level of family support was assessed by using family support questionnaires proposed by Friedman and the quality of life of the respondents was measured using the SQLS questionnaires. The findings showed that good and moderate family supports have the same percentage of 35.9%, while the results of the quality of life score showed that the majority of respondents had good quality of life (82.1%). Based on the analysis by using Spearman-Rank test, there is a significant correlation between family support and quality of life of respondents with p = 0,000 (p <0,05) and strong correlation value of 0.618 and positive correlation direction which means if family support increases then the quality of life of respondents will increase and vice versa. The future researchers are expected to exercise control over other factors that may affect the quality of life of People with Mental Disorders (ODGJ).